2019
DOI: 10.21037/atm.2019.12.73
|View full text |Cite
|
Sign up to set email alerts
|

Plasma inorganic pyrophosphate and alkaline phosphatase in patients with pseudoxanthoma elasticum

Abstract: Background: Inorganic pyrophosphate (PPi) plays a major role inhibiting dystrophic calcification. The aim was to analyze levels of PPi in patients having pseudoxanthoma elasticum (PXE), and controls as well as the enzymes who regulate the PPi plasma concentration.Methods: We collected fasting blood samples from PXE patients and age-and sex-matched controls in ethylenediamine tetraacetic acid (EDTA) and citrate-theophylline-adenosine-dipyridamole (CTAD) containing tubes. We measured PPi, ENPP1 mass and activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 30 publications
3
36
1
Order By: Relevance
“…The latter may partly contribute to the decreased PPi plasma levels observed in PXE patients, similar to what has been suggested for higher TNAP activity seen in PXE patients. Indeed, S anchez-T evar et al showed that TNAP activity was inversely correlated with plasma levels of PPi [50].…”
Section: Abcc6-associated Interactomementioning
confidence: 99%
See 2 more Smart Citations
“…The latter may partly contribute to the decreased PPi plasma levels observed in PXE patients, similar to what has been suggested for higher TNAP activity seen in PXE patients. Indeed, S anchez-T evar et al showed that TNAP activity was inversely correlated with plasma levels of PPi [50].…”
Section: Abcc6-associated Interactomementioning
confidence: 99%
“…Indeed, Sánchez‐Tévar et al . showed that TNAP activity was inversely correlated with plasma levels of PPi [50].…”
Section: The Human Abcc6 Genementioning
confidence: 99%
See 1 more Smart Citation
“…The latter is a powerful physiological antimineralization factor which interferes with hydroxyapatite crystal growth by binding to the initial nucleus of mineralization and preventing calcium phosphate deposition. In patients with PXE with nonfunctional ABCC6, the plasma levels of PPi are reduced to about 40% of the level in normal healthy individuals, which is reproducibly in the range of 1 µM measured by using a number of analytical techniques [ 12 , 13 ]. Reduced PPi levels then allow the growth of calcium hydroxyapatite crystal deposits on the surfaces of the extracellular matrix, particularly the elastic structures.…”
Section: Introductionmentioning
confidence: 99%
“…The human Abcc6 gene belongs to the ABCC family and codifies for the MRP6 protein, mainly expressed at the basolateral membrane of hepatocytes [4]. More than 300 mutations in Abcc6 such as deletions, insertions, or substitutions, mostly occurring in the sequence encoding the nucleotide binding domains, are associated with the Pseudoxanthoma elasticum, an autosomal recessive disease characterized by a progressive ectopic calcification [5][6][7]. Studies aimed at understanding the molecular mechanisms underlying the observed phenotype have shown that ABCC6 contributes to the outflow of ATP from cells [8,9].…”
Section: Introductionmentioning
confidence: 99%